Can Social Safety Nets Alleviate Seasonal Deprivation? Evidence from Northwest Bangladesh - Khandker, Shahidur R.; Khaleque, M. Abdul; Samad, Hussain A. (2012)
This paper examines the role of social safety-net programs in Bangladesh run by the government and nongovernmental organizations to mitigate seasonal deprivation in the country's highly vulnerable northwest region. Specifically, the paper explores whether social safety nets are limited to averting seasonal deprivation or can also address seasonality of income and employment more generally. Using a recent survey from the greater Rangpur (northwest) region, the paper finds that social safety nets have a positive effect on mitigating both seasonal and non-seasonal food deprivation. The results are robust, owing to the recent expanded coverage of social safety-net programs run by nongovernmental organizations active in the region. But given the annual recurrence of monga (seasonal food insecurity) in the northwest region owing to agricultural seasonality and an overwhelming dependence on agriculture for livelihoods, social safety nets are not a reliable tool for monga eradication. Programs are also needed to promote the income and productivity of the poor through diversification of income and employment.